2006
DOI: 10.1007/s10310-006-0222-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of soil carbon and nitrogen storage and forest productivity in a watershed planted to Japanese cedar (Cryptomeria japonica D. Don)

Abstract: Digital terrain modeling was used to evaluate landscape-level spatial variation of soil C and N storage and site productivity in Japanese cedar (Cryptomeria japonica D. Don) stands. Soil C and N storage were measured in samples from surface soils (0-25 cm depth) of 29 Japanese cedar stands in the 205-ha Myougodani watershed, Toyama Prefecture. The site index (C. japonica tree height at age 40 years) was used as a measure of forest productivity. Seven terrain attributes (elevation, slope gradient, aspect, profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
14
1
Order By: Relevance
“…The author's previous study (Zushi 2006) revealed that a linear regression model using wetness index and openness derived from digital terrain analysis as explanatory variables could explain reasonably well the spatial variation in productivity of Japanese cedar forests within a 205 ha watershed in Himi city. In particular, wetness index, which represents the redistribution of soil water within a landscape by lateral flow, explained 58% of the total variation in cedar productivity.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The author's previous study (Zushi 2006) revealed that a linear regression model using wetness index and openness derived from digital terrain analysis as explanatory variables could explain reasonably well the spatial variation in productivity of Japanese cedar forests within a 205 ha watershed in Himi city. In particular, wetness index, which represents the redistribution of soil water within a landscape by lateral flow, explained 58% of the total variation in cedar productivity.…”
Section: Discussionmentioning
confidence: 98%
“…In a previous study (Zushi 2006) the author discovered strong correlations between environmental factors derived from digital terrain analysis and site productivity of Japanese cedar (Cryptomeria japonica D. Don) in a relatively small watershed (205 ha). These correlations proved to have good predictive utility.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In natural ecosystems, nutrition levels showed great spatial heterogeneity at a range of scales, from meters to centimeters (Jackson and Caldwell, 1993;Boerner et al, 2000;Jonson et al, 2001;Rietkerk et al, 2002;Schreiner, 2005;Zushi, 2006;Knyazhneva et al, 2006). Roots manifest high plasticity in response to the nutrition spatial heterogeneity because of their chemotaxis, resulting in great changes in root traits and root system architecture (Ahlström et al, 1988;Fitter and Stickland, 1991;Robinson, 1994), and meanwhile the changes in the spatial heterogeneity affected fine root longevity and turnover (Majdi and Andersson, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have shown that stem productivity or height growth (site index) in Japanese forests is related to topography (Enoki et al 1996;Tateno and Takeda 2003;Zushi 2006) and soil type (Inoue et al 1973;Mashimo 1960). These studies suggest that soil water and nitrogen availability are the primary factors that determine stem productivity.…”
Section: Introductionmentioning
confidence: 99%